STIMULAREA AUTONOMIEI STUDENTULUI, VERIGĂ DE BAZĂ ÎN FORMAREA PROFESIONALĂ - Nița, Mariana (CEP USM, 2018)
The acquisition of knowledge depends on our targets, the environment and the culture we are brought up. That is why how or what is the best way to teach English still remains to be unquestionable. Due to the publication of the Common European Framework of Reference for Languages: Learning, Teaching, Assessment, nowadays each teacher, each institution and even each student knows what their needs are, their objectives, what and how they have to learn, and what steps they have to take in order to achieve their targets and a resounding success. Yet, there is a lot to be discussed about all these issues. Everyone is taking a deep interest in findind the best answer to what and how we have to teach for a successful outcome and integration into modern society.
Keywords: learning styles; cognitive needs; linguistic knowledg; e-licensing; instruirea interactivă; motivarea; dezvoltarea competențelor